ADVANTAGE ASPECTS OF INNOVATIVE TECHNOLOGIES IN IMPROVING EDUCATIONAL EFFICIENCY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In the current boskich of the development of our republic, it is determined by the fact that fundamental qualitative changes are being made in all aspects of the life of our society. It is an undeniable fact that the solution to this huge task is carried out in connection with the increase in the mental potential of our citizens. The article explores the importance of innovative technologies in education.